2010
DOI: 10.1111/j.1745-4565.2010.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Enumeration of Microorganisms in Ready‐to‐eat Foods, Ready‐to‐cook Foods and Fresh‐cut Produce in Korea

Abstract: Levels of total aerobic plate counts (APC), coliforms and various pathogens in convenient foods including ready‐to‐eat foods (RTE), ready‐to‐cook foods (RTC) and fresh‐cut produce (FCP) in Korea were investigated. A total of 244 samples comprising 145 samples of RTE, 39 samples of RTC and 60 samples of FCP were purchased from hyper chain stores located in six different provinces. APC levels of RTE showed a relatively wide range of 1.9–7.8 log10cfu/g, while APC levels of RTC and FCP were relatively high at 6.3–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 10 publications
2
5
2
Order By: Relevance
“…Unlike Listeria monocytogenes (Shi et al, 2015 ) and Salmonella (Yang et al, 2016 ) , V. parahaemolyticus was not frequently detected on RTE foods. Previous study reported that no V. parahaemolyticus was positive in 145 samples of RTE food in Korea (Chung et al, 2010 ), similar result was found in Iran (Zarei et al, 2012 ). However, a report indicated that the prevalence of V. parahaemolyticus in RTE foods was an important cause of food poisoning in Shanghai, China (Tian et al, 2008 ).…”
Section: Discussionsupporting
confidence: 77%
“…Unlike Listeria monocytogenes (Shi et al, 2015 ) and Salmonella (Yang et al, 2016 ) , V. parahaemolyticus was not frequently detected on RTE foods. Previous study reported that no V. parahaemolyticus was positive in 145 samples of RTE food in Korea (Chung et al, 2010 ), similar result was found in Iran (Zarei et al, 2012 ). However, a report indicated that the prevalence of V. parahaemolyticus in RTE foods was an important cause of food poisoning in Shanghai, China (Tian et al, 2008 ).…”
Section: Discussionsupporting
confidence: 77%
“…Enteritidis in Study 2, is lower than the prevalence rates of Salmonella (2.0–19.7%) and E. coli (6.0–51.5%), reported from Africa (Cardinale et al, ; Eromo et al, ; Mosupye & von Holy, ; Muhammad et al, ; Wolde Bereda, Emerie, Reta, & Asfaw, ). It is also lower than the prevalence of E. coli (4.1%) and Salmonella (4%) reported from South Korea (Chung, Kim, & Ha, ), while comparable with the prevalence data reported for the United States (Levine, Rose, Green, Ransom, & Hill, ) and Trinidad and Tobago (Hosein et al, ). This low prevalence of these specific pathogens in RTE foods in Barbados may be as a result of two important factors, the institution of a local Codex committee that ensures that International Codex standards are followed by food safety regulators on the island and the annual required food safety training for food handlers by the Ministry of Health (Hull‐Jackson, ; Ministry of Industry, International Business, Commerce and Small Business Development, ).…”
Section: Discussionsupporting
confidence: 80%
“…Unsatisfactory levels of coliforms (≥4 log 10 CFU/g) were present in 4.2% of RTE foods from Barbados. This is lower than what was reported from Korea (12.4%; Chung et al, ) and Nigeria (100%; Nkere et al, ), but higher than in Italy (0.0%; Catellani, Alberghini, Feletti, & Boldrin, ). Coliforms are expected to be present in many raw foods such as vegetables.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The increasing amounts of street foods and the increasing demand for minimally processed ready-to-eat products have begun to concern public health agencies on food safety assurance (Lee et al, 2014 ). Foodborne pathogens are present in various foods such as fruits, vegetables and ready-to-eat products which are consumed without any further treatment (Chung et al, 2010 ; Lee et al, 2014 ). This may lead to foodborne diseases if food safety issues are not taken into consideration.…”
Section: Introductionmentioning
confidence: 99%